Toll-like Receptor 4 in Acute Kidney Injury - Garramuño, Patricia (2023)
Abstract: Acute kidney injury (AKI) is a common and devastating pathologic condition, associated with considerable high morbidity and mortality. Although significant breakthroughs have been made in recent years, to this day no effective pharmacological therapies for its treatment exist. AKI is known to be connected with intrarenal and systemic inflammation. The innate immune system plays an important role as the first defense response mechanism to tissue injury. Toll-like receptor 4 (TLR4) is a well-characterized pattern recognition receptor, and increasing evidence has shown that TLR4 mediated inflammatory response, plays a pivotal role in the pathogenesis of acute kidney injury. Pathogen-associated molecular patterns (PAMPS), which are the conserved microbial motifs, are sensed by these receptors. Endogenous molecules generated during tissue injury, and labeled as damage-associated molecular pattern molecules (DAMPs), also activate pattern recognition receptors, thereby offering an understanding of sterile types of inflammation. Excessive, uncontrolled and/or sustained activation of TLR4, may lead to a chronic inflammatory state. In this review we describe the role of TLR4, its endogenous ligands and activation in the inflammatory response to ischemic/reperfusion-induced AKI and sepsis-associated AKI. The potential regeneration signaling patterns of TLR4 in acute kidney injury, are also discussed.